The use of cytokines in the treatment of cornea inflammatory and dystrophic diseases (review) - M. S. Denisko; O. I. Krivosheina (Сибирский научный медицинский журнал)
Cytokines are unique biologically active substances that form the system of regulation of basic body functions that simultaneously with the nervous and endocrine systems maintain homeostasis under adverse conditions – the introduction of pathogens or violation of the integrity of tissues. Cytokines regulate the amplitude and duration of inflammatory and immune responses, so they are produced and secreted transiently and have a short half-life. These biologically active substances act in very low concentrations. At the same time, the main properties of cytokines are pleiotropy, lack of antigenic specificity, and the ability to form a cascade chain, that allows versatile correction of the spectrum of reparative processes. There are evidences of the possibility of using cytokines in the regeneration of damaged tissues in recent decades. In this connection, a new vector of search for pathogenetically directed ways to improve and restore lost functions using both individual representatives of cytokines and their natural complex is determined. The article reflects the basic information about the influence of cytokines on the development of various diseases of the cornea, as well as the methods of cytokine therapy in the treatment of these pathologies and prospects for their development.